Effective Thermal Conductivity of Typical Composite Plate with Inner Heat Source and Temperature Difference. (3rd August 2022) - Liu, Ziping; Ji, Yu; Zhang, Han; Sun, Jun
Abstract: Composite materials are essential in various energy fields owing to their improved heat transfer characteristics. Due to their inhomogeneous structure, it is difficult to obtain the heat transfer details. Effective thermal conductivity (ETC) is an important lumped thermal parameter used to analyze the heat transfer process in composite materials. Existing ETC models are derived by applying a temperature difference (TD) on two opposite boundaries of the composite material to induce heat flow. However, for some composite materials, such as nuclear fuels, the effect of the inner heat source (IHS) is typically ignored. Thus, the suitability of using ETC models based on a TD scheme for composite materials with IHS still requires further investigation. In this study, first the conserved quantities of ETC of the TD and IHS schemes were determined. For normal materials of the TD scheme, the conserved quantity of ETC can be selected as heat flow, whereas for nuclear fuels of the IHS scheme, the average temperatures are recommended as the conserved quantity. Then the general ETC models for composite plate were derived considering both the TD and IHS schemes and special cases with either TD or IHS were also analyzed. Finally, based on the results of this study, the idea of studying the ETC of tristructural-isotropic or TRISO particle-based nuclear fuels is proposed.